Outcome of Tumor-Associated Proptosis in Patients With Spheno-Orbital Meningioma: Single-Center Experience and Systematic Review of the Literature - Schneider, Matthias; Potthoff, Anna-Laura; Borger, Valeri; Hadjiathanasiou, Alexis; Schäfer, Niklas; Güresir, Ági; Vatter, Hartmut; Herrlinger, Ulrich; Güresir, Erdem; Schuss, Patrick (Frontiers in Oncology, 2020)
Object: Tumor-associated proptosis comprises a frequent phenomenon that negatively impacts patient quality of life in patients suffering from spheno-orbital meningioma (SOM). Therefore, proptosis outcome represents an important measure in meningioma surgery. In the current study we analyzed our institutional database in order to evaluate the recovery of tumor-associated proptosis in patients with SOM. Methods: Between 2009 and 2019, 32 patients with SOM underwent surgical treatment at the authors´ institution. The exophthalmos index (EI) was calculated by means of pre- and postoperative tumor-associated proptosis. Patients with preoperative EI≥1.1 were included in further analysis. Further, we performed a systematic review of the contemporary literature. Favorable proptosis outcome was defined as postoperative decreased EI compared to preoperative EI. Results: Overall, 25 of 32 patients with SOM (78%) suffered from preoperative proptosis in the present series. Preoperative mean EI of 1.37±0.18 decreased after surgical treatment to a postoperative mean EI of 1.15±0.1 during follow-up (p<0.0001). Systematic review of the literature revealed 3 studies with individual data on pre- and postoperative EI measurements leading to a total of 103 patients. 100 of 103 patients (97%) with SOM and preoperative proptosis achieved favorable outcome. Conclusions: The exophthalmos index provides a comparable standard in evaluation of surgical outcome in patients with tumor-associated proptosis due to spheno-orbital meningiomas. The large dataset consisting of pooled individual patient data from the systematic review of the literature and the present case series support the assumption that surgical treatment is highly effective in treatment of tumor-associated proptosis in spheno-orbital meningioma.